2016
DOI: 10.18483/ijsci.763
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Incrimination Rates of Two Minor Vectors - Anopheles Gambiae and Anopheles Funestus Complexes in the Transmission of Bancroftian Filariasis in Makurdi, North Central Nigeria

Abstract: Abstract:Studies on the roles of Anopheles gambiae and Anopheles funestus complexes in the transmission of Wuchereria bancrofti in Makurdi, Nigeria across four localities: High-level, Wurukum, North-bank and Wadata were undertaken from July, 2011 to June, 2012. 1,681 adult female mosquitoes were identified and dissected with the aid of standard keys and procedures to determine their incrimination rates with microfilariae of Wuchereria bancrofti. 1,040 (61.87%) of these were Anopheles gambiae sensu lato while 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…gambiae in this study could be attributed to the fact that the communities studied are situated in close proximity to freshwater bodies thereby providing favourable breeding grounds for these mosquitoes as compared to the culicines which prefer polluted breeding grounds. The high abundance of Anopheles species reported in this study conforms to the findings conducted in other parts of Nigeria (Dogara et al, 2012;Manyi et al, 2014b;Ezihe et al, 2017) which recorded a higher prevalence of Anopheles species in their studies. Ombugadu (2020a) also reported a high abundance of An.…”
Section: Discussionsupporting
confidence: 92%
“…gambiae in this study could be attributed to the fact that the communities studied are situated in close proximity to freshwater bodies thereby providing favourable breeding grounds for these mosquitoes as compared to the culicines which prefer polluted breeding grounds. The high abundance of Anopheles species reported in this study conforms to the findings conducted in other parts of Nigeria (Dogara et al, 2012;Manyi et al, 2014b;Ezihe et al, 2017) which recorded a higher prevalence of Anopheles species in their studies. Ombugadu (2020a) also reported a high abundance of An.…”
Section: Discussionsupporting
confidence: 92%
“…funestus sl) in both seasons. Similar observation have been observed elsewhere by Manyi et al, (2016). These observations probably depicted Anopheles spp.…”
Section: Discussionsupporting
confidence: 92%
“…This could account for its low contribution to infectivity rates. Previous works have posited that it is an urban vector Manyi et al (2014) in Makurdi (North Central, Nigeria) found high infectivity rates in Anopheles and its involvement together with Anopheles spp. in Abakiliki further supports changed sanitary condition of the area.…”
Section: Discussionmentioning
confidence: 98%